Nowe kompetencje Trybunału Roty Rzymskiej - Góralski, Wojciech (Biuletyn Stowarzyszenia Kanonistów Polskich, 2013)
On 30 August 2011 Pope Benedict XVI issued motu proprio “Quaerit semper” ( came in to force on 1 October of the same year ), pursuant to which he transferred competences concerning obtaining super rato et non consummato dispensation and cleelaring invalidity of holy orders – from Congregation for Divine Worship and the Discipline of the Sacraments to the Tribunal of the Roman Rota by establishing a new office in this Tribunal. The introductory part of motu proprio contains motives of introduced innovations (among others directives of II Vatican Council), and the second part contains proper legal dispositions (in four articles), which amend provisions of Pastor bonus, Apostolic Constitution by John Paul II of 28 June 1988.